Vascularization of the Dorsal base of the second metacarpal bone: an anatomical study using C-arm cone beam computed tomography - Bermel, Christina; Kneser, Ulrich (Plastic and reconstructive surgery, 2014)
Background: Vascularized bone grafts of the hand are a promising option for treatment of hand abnormalities. Therefore, the purpose of this study was to analyze the arterial anatomy of the dorsal aspect of the second metacarpal base to further investigate this possible donor site for bone grafts. Methods: The authors examined 16 fresh frozen cadaveric hands by using a C-arm cone beam computed tomography scanner and depicted the three-dimensional course of the second dorsal metacarpal artery and measured the diameter, length, and arc of rotation of this nutritive vessel. In addition, the authors dissected six of the hands under a dissecting microscope and, after selective injection of gelatin dye solution, the authors analyzed the vessel entrances into the bones histologically.Results: In all examined hands, the second dorsal metacarpal artery was a nutritive vessel to the dorsal base of the second metacarpal. The average diameter was 1.3 ± 0.4 mm and the average length of the vascular pedicle was approximately 3.3 ± 0.3 cm. In 14 of 16 cases, the arc of rotation was sufficient to reach the lunate without difficulty. Histologic analysis showed an intrinsic blood supply in the donor region with a vessel diameter of approximately 58 μm. A clinical case with application in Kienböck disease is presented. Conclusion: Pedicled vascularized bone grafts from this area are suitable for clinical application to treat Kienböck disease if standard donor sites are unavailable.